The Impact of Village Funds, Locally-Generated Revenue (PAD), Capital Expenditure, and TPT on Poverty in East Java (2020–2024) - Nadella, Nadella; Eviana Hutabarat, Ruth (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2025)
Poverty remains a critical challenge within the Sustainable Development Goals (SDGs) framework, despite numerous intervention programs having been implemented. Although East Java Province contributes significantly to the national gross regional domestic product (GRDP), poverty levels remain high, especially in rural areas. This study aims to analyze the influence of village funds, capital expenditure, local own-source revenue (PAD), and the open unemployment rate (TPT) on poverty levels across regencies and cities in East Java from 2020 to 2024. The method employed is panel data regression using the Fixed Effects Model (FEM), based on secondary data from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance (DJPK). The results indicate that village funds and PAD have a significant negative effect on poverty. In contrast, capital expenditure has no significant effect, while TPT has a considerable positive impact on poverty in the regencies and cities of East Java Province.